Toxoplasma gondii is dependent on glutamine and alters migratory profile of infected host bone marrow derived immune cells through SNAT2 and CXCR4 pathways - De Miguel, Zurine (2014)
The obligate intracellular parasite, Toxoplasma gondii, disseminates through its host inside infected immune cells. We hypothesize that parasite nutrient requirements lead to manipulation of migratory properties of the immune cell. We demonstrate that 1) T. gondii relies on glutamine for optimal infection, replication and viability, and 2) T. gondii-infected bone marrow-derived dendritic cells (DCs) display both “hypermotility” and “enhanced migration” to an elevated glutamine gradient in vitro. We show that glutamine uptake by the sodium-dependent neutral amino acid transporter 2 (SNAT2) is required for this enhanced migration. SNAT2 transport of glutamine is also a significant factor in the induction of migration by the small cytokine stromal cell-derived factor-1 (SDF-1) in uninfected DCs. Blocking both SNAT2 and C-X-C chemokine receptor 4 (CXCR4; the unique receptor for SDF-1) blocks hypermotility and the enhanced migration in T. gondii-infected DCs. Changes in host cell protein expression following T. gondii infection may explain the altered migratory phenotype; we observed an increase of CD80 and unchanged protein level of CXCR4 in both T. gondii-infected and lipopolysaccharide (LPS)-stimulated DCs. However, unlike activated DCs, SNAT2 expression in the cytosol of infected cells was also unchanged. Thus, our results suggest an important role of glutamine transport via SNAT2 in immune cell migration and a possible interaction between SNAT2 and CXCR4, by which T. gondii manipulates host cell motility.